Peer review of the pesticide risk assessment of the active substance sulfur - European Food Safety Authority (EFSA); Fernando Alvarez; Maria Arena; Domenica Auteri; Marco Binaglia; Anna Federica Castoldi; Arianna Chiusolo; Angelo Colagiorgi; Mathilde Colas; Federica Crivellente; Chloe De Lentdecker; Isabella De Magistris; et al. (EFSA Journal)
Abstract The conclusions of EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State France and co‐rapporteur Member State Slovenia for the pesticide active substance sulfur and the considerations as regards the inclusion of the substance in Annex IV of Regulation (EC) No 396/2005 are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012, as amended by Commission Implementing Regulation (EU) No 2018/1659. The conclusions were reached on the basis of the evaluation of the representative uses of sulfur as a fungicide and acaricide on grapevine and cereals (wheat, barley, oat, rye, triticale). The reliable end points, appropriate for use in regulatory risk assessment, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are reported where identified.